Computed tomographic evaluation of inflammatory sinonasal diseases - Kandukuri, Rashmi; Phatak, Suresh (International Journal of Research in Medical Sciences, 2017)
Background: Computed Tomography plays a major diagnostic role in patients with inflammatory sinonasal diseases and determines the mode of management by displaying the complex osteomeatal anatomy, determining anatomical variations, extent of disease and characterizing various inflammatory sinonasal diseases. Purpose of the study was to assess the role of CT in evaluation of inflammatory sinonasal diseases by evaluating the sensitivity and specificity of CT in diagnosis of various inflammatory Sinonasal diseases. Methods: In this hospital based prospective study 122 patients with symptomatic inflammatory sinonasal diseases were evaluated by 16 slice MDCT. CT diagnosis is correlated with final diagnosis obtained from findings of nasal endoscopy/Functional Endoscopic Sinus Surgery, histopathological examination and fungal culture. Statistical analysis was done by descriptive and inferential statistics using Test statistics (sensitivity, specificity, PPV, NPV and accuracy) and Z test for single proportions (Z value >1.96 is considered significant). Software used in the analysis was SPSS 17.0 version and graph pad prism 6.0 version and p <0.05 is considered as level of significance. Results: On correlating CT diagnosis with final diagnosis, Chronic Sinusitis had 98.41% sensitivity and 96.61% specificity, fungal sinusitis had 66.67% sensitivity and specificity 99.14%, polyps had sensitivity of 94.59% and specificity of 97.6%, the rest of the inflammatory conditions had sensitivity 93.7 % and 99% specificity. P value in all instances was <0.05, i.e. <0.0001, indicating the significance of the findings. Conclusions: CT is the diagnostic modality of choice in evaluation of various inflammatory pathologies and associated complications thereby planning the further management of the patient.